Upaya Peningkatan IPM Dari Sisi Pendidikan Pada Masyarakat Johar Baru Jakarta Pusat - Indri Arrafi Juliannisa; MB Nani Ariani; Tri Siswantini (IKRA-ITH ABDIMAS, 2023)
In a life for a person/individual to be able to live well, it cannot be separated from what is attached to himself that he has, without having to need the help of others, namely a science, creation/idea. Ability and desire, all of which will not be achieved or possessed, if we are very lacking or even do not have it at all because we cannot read, write and count which we know as illiteracy. With the current condition that everything is digital or technological progress, it is very unfortunate if there are still an area or village whose people are illiterate, so that the village can be said to have a shortage or difficulty in their lives, even the impact will eventually reduce economic growth a country. Then how can the village that is left behind, to be able to progress and develop at least for the consumption of himself and his family does not lack, it is necessary to have public awareness that has education, innovation, knowledge and ability to be able to help it. So that they can be released from continuous suffering, if there is no help from outside the area. Therefore, we, from the Lecturer team of Educational Institutions from Universitas Pembangunan Veteran Jakarta, are very moved to invite the village/regional community to want to participate and support educational institution programs in a community service activity in the context of implementing the eradication of illiteracy in early childhood in the village of Johar Baru. By conducting training in the teaching and learning process for those who cannot read, write and count, so that they can help government programs, namely improving education in the context of poverty eradication programs.